Strategies to Improve Service Quality Through Digitalization of Banking Services at PT. Bank Negara Indonesia (Persero) Tbk - Daga, Rosnaini; Nawir, Fadliyani; Pratiwi, Dhita (Yayasan Ahmar Cendekia Indonesia, 2021)
The strategy of improving service quality through the digitalization of services is a strategy that a company uses to develop digital-based services to answer consumers' increasingly digital needs. Likewise, the banking business continues to innovate to improve the quality of its services. The digitization of banking services is one strategy that can answer problems that occur in terms of improving the quality of banking services. PT. Bank Negara Indonesia Central Jakarta has implemented digitalization of services for the last 3 (three) years. It can be seen from the annual report and internal interviews that Bank Negara Indonesia has achieved good performance targets. However, several obstacles are faced in implementing the digitalization strategy for services such as legacy IT systems. This work culture is not yet digital and poor coordination between BNI's internal divisions. Some of these things need to be considered more seriously to achieve PT. Bank Negara Indonesia's vision and mission.